ANALISIS SIKAP TOLERANSI MASYARAKATMELALUI KEGIATAN GOTONG ROYONG DI DESA HILIZAMURUGO KECAMATAN SUSUA KABUPATEN NIAS SELATAN TAHUN 2021 - Adilah Laia; Fatolosa Hulu (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aims 1) to determine the tolerance attitude of the community through mutual cooperation activities in Hilizamurugo Village, Susua District, South Nias Regency. 2) to find out the implementation of gotong royong in Hilizamurugo Village, Susua District, South Nias Regency. The research method used is qualitative by using data collection techniques in the form of observation, interviews and documentation with data source information from respondents: village heads, community leaders, and the community to confirm the validity of the data obtained. From the results of the study, it was found that the shifting factors in the values ​​of gotong royong in the Hilizamurugo village community were 1) the occurrence of a shift in the attitude of community tolerance through mutual cooperation activities in the Hilizamurugo village community, Susua sub-district, South Nias district caused by several factors such as daily activities, the existence of a system wages/salaries, and there is a heavy feeling of calling or gathering residents to work together. 2) the implementation of gotong royong in Hilizamurugo village, Susua sub-district, South Nias district is strongly influenced by the role of community leaders who always urge and motivate the community to always participate in gotong royong activities. From the explanation above, it can be concluded that the role of community leaders is to always urge the community to continue to do mutual cooperation, both mutual cooperation and mutual cooperation, please help so that the values ​​of togetherness, cooperation between members of the community can be better, prioritizing common interests above personal interests. , help each other selflessly and always maintain and maintain the values ​​of gotong royong which are the legacy of previous parents.